Reduction of stillbirths in England from 2008 to 2017 according to uptake of the Growth Assessment Protocol: 10‐year population‐based cohort study. (1st March 2021) - Hugh, O.; Williams, M.; Turner, S.; Gardosi, J.
ABSTRACT: Objective: Antenatal detection of small‐for‐gestational age (SGA) can reduce significantly the risk of stillbirth. The Growth Assessment Protocol (GAP) was developed to address the problem that most SGA fetuses are missed antenatally. We set out to analyze the effect that the GAP program has had on stillbirth rates in England. Methods: We analyzed data from 2008 (the year before roll‐out of the GAP program) to 2017 (latest available Office for National Statistics (ONS) unit‐based data). The program consists of five elements: training, evidence‐based guidelines for risk assessment and surveillance of fetal growth, customized charts, recording of process and outcome indicators, and audit of missed SGA cases. All maternity units in England were categorized into one of three groups according to their GAP status in 2017: (1) not in the GAP program; (2) GAP implemented partially (incomplete adoption of protocol, no monitoring and audit); and (3) GAP implemented completely. A subset of the complete‐implementation group comprised the 20 units with the highest SGA detection rates. Unit‐level live‐birth and stillbirth data were obtained from the ONS for each of these groups. Results: Stillbirth rates declined across all groups from 2008 to 2017, and significantly more in units in which GAP was implemented completely than in the non‐GAP units ( P < 0.05). The steepest decline in stillbirth rate was observed in the 20 units with the highest SGA detection rates, which had a 24% lower stillbirth rate compared with the units not using GAP ( P < 0.01) in 2017. This difference remained significant after mixed‐effects logistic regression analysis of potential confounding, including social deprivation (odds ratio, 0.76 (95% CI, 0.64–0.90)). Assessment of the nine Bradford Hill causality criteria and associated characteristics suggested that the association between implementation of the GAP program and reduction in stillbirth rate was causal. Conclusions: There has been an overall reduction in stillbirth rates in England that is likely to be a result of increased awareness of the importance of antenatal detection of SGA as a key risk factor for stillbirth. The decline in stillbirth rates was significantly greater in maternity units that had fully implemented the GAP program, and was most pronounced in the units with the highest antenatal SGA detection rates. © 2020 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.